Optimalisasi WAPA HIMMAH NW: Preparasi Kader dalam Menghadapi Tantangan Organisasi dan Masyarakat - Sunardi, Sunardi; Halimatuzzahrah, Halimatuzzahrah; Harmonika, Sri; Mukminin, Emha Zainul; Junaidi, M. (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2025)
HIMMAH NW as a student organization born in the region, continues to struggle to maintain its existence in the midst of competition with other national student organizations. One of the strategies used to attract new members is through needs analysis in the recruitment and debriefing process of new members, known as WAPA HIMMAH NW. This program not only serves as a formal orientation, but also as a preparation for members to play an active role in the organization and contribute to society. In order to support cadre capacity building, HIMMAH NW activities are implemented using the Community-Based Participatory Research (CBPR) approach, which involves cadres in every stage, from planning to program implementation. This approach includes four main stages: foundation laying, research planning, information collection and analysis, and follow-up of findings, which aim to improve cadres' skills in facing organizational and social challenges. Through this approach, it is expected to create cadres who are not only proficient in organizing, but also have high integrity and adaptability